2017
DOI: 10.1074/jbc.m117.813923
|View full text |Cite
|
Sign up to set email alerts
|

The NQO1 bioactivatable drug, β-lapachone, alters the redox state of NQO1+ pancreatic cancer cells, causing perturbation in central carbon metabolism

Abstract: Many cancer treatments, such as those for managing recalcitrant tumors like pancreatic ductal adenocarcinoma, cause off-target toxicities in normal, healthy tissue, highlighting the need for more tumor-selective chemotherapies. β-Lapachone is bioactivated by NAD(P)H:quinone oxidoreductase 1 (NQO1). This enzyme exhibits elevated expression in most solid cancers and therefore is a potential cancer-specific target. β-Lapachone's therapeutic efficacy partially stems from the drug's induction of a futile NQO1-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 57 publications
10
68
0
Order By: Relevance
“…Reduction activates this anticancer compound [161] Quinone epoxides Potentially important if members of this group of compounds used as drugs. [162] β-lapachone Futile cycling involving NQO1 results in reduced cellular concentrations of NAD(P)H contributing to cell death [163,164] Mitomycin C Reduction activates this akylating cytotoxic drug [165,166] Tirapazamine and other heteroaromatic N-oxides Slow reaction. Superoxide also produced [167] Benzofuroxans Reduction by NQO1 may play a minor role in cytotoxicity [168] Nitroaromatics Reactivity correlates with electrode potential [169,170] Aminochrome Reaction is important in protection against Parkinson's Disease and other neurological diseases [171,172] Inhibitors Dicoumarol and derivatives thereof High affinity; competes with NAD(P)H; negatively cooperative; often used in experimental studies; derivatives may be anticancer lead compounds; dissociates NQO1-p53 complexes resulting in increased p53 degradation and inhibition of apoptosis [143,151,154,156,173,174] Curcumin May dissociate NQO1-p53 complexes resulting in increased p53 degradation and inhibition of apoptosis.…”
Section: Compound Comments Referencesmentioning
confidence: 99%
“…Reduction activates this anticancer compound [161] Quinone epoxides Potentially important if members of this group of compounds used as drugs. [162] β-lapachone Futile cycling involving NQO1 results in reduced cellular concentrations of NAD(P)H contributing to cell death [163,164] Mitomycin C Reduction activates this akylating cytotoxic drug [165,166] Tirapazamine and other heteroaromatic N-oxides Slow reaction. Superoxide also produced [167] Benzofuroxans Reduction by NQO1 may play a minor role in cytotoxicity [168] Nitroaromatics Reactivity correlates with electrode potential [169,170] Aminochrome Reaction is important in protection against Parkinson's Disease and other neurological diseases [171,172] Inhibitors Dicoumarol and derivatives thereof High affinity; competes with NAD(P)H; negatively cooperative; often used in experimental studies; derivatives may be anticancer lead compounds; dissociates NQO1-p53 complexes resulting in increased p53 degradation and inhibition of apoptosis [143,151,154,156,173,174] Curcumin May dissociate NQO1-p53 complexes resulting in increased p53 degradation and inhibition of apoptosis.…”
Section: Compound Comments Referencesmentioning
confidence: 99%
“…β-Lapachone (β-lap), as a quinone-containing compound derived from the lapacho tree located in South America, is bioactivated by NAD(P)H: quinone oxidoreductase 1 (NQO1). Recently, its effects on energy metabolism due to NAD + depletion on pancreatic ductal adenocarcinoma (PDA) have been shown [43]. Based on the combined GC/MS and 1 H NMR metabolomics analysis of MiaPaCa2 cells in vitro, β-lap treatment was found to decrease the NAD-sensitive pathways, such as glycolysis and TCA cycle, which revealed that targeting NQO1 may sensitize the treatment of β-lap.…”
Section: Review On Metabolism-targeting Chinese Medicine Treatment Onmentioning
confidence: 99%
“…The NRF2 target gene NAD(P)H:quinone oxidoreductase 1 (NQO1) is a two-electron oxidoreductase involved in the detoxification of quinones using NADH or NADPH to generate the corresponding hydroquinone derivative (8). Increased expression of NQO1 has been observed in many solid tumors, has been shown to occur early in tumorigenesis, and has been linked to multiple carcinogenic processes (9)(10)(11)(12)(13)(14)(15). For example, increased NQO1 expression is observed in precursor lesions (pancreatic intraepithelial neoplasia) and further increased expression occurs in invasive pancreatic ductal adenocarcinoma (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of NQO1 has been observed in many solid tumors, has been shown to occur early in tumorigenesis, and has been linked to multiple carcinogenic processes (9)(10)(11)(12)(13)(14)(15). For example, increased NQO1 expression is observed in precursor lesions (pancreatic intraepithelial neoplasia) and further increased expression occurs in invasive pancreatic ductal adenocarcinoma (13)(14)(15). The ability of NQO1 to generate hydroquinones, combined with its overexpression in many cancers, has been utilized as a therapeutic strategy, and various anticancer compounds that are bioactivated by NQO1 have been developed.…”
Section: Introductionmentioning
confidence: 99%